Cancer cells exploit an orphan RNA to drive metastatic progression. (November 2018) - Fish, Lisa; Zhang, Steven; Yu, Johnny; Culbertson, Bruce; Zhou, Alicia; Goga, Andrei; Goodarzi, Hani
Abstract Here we performed a systematic search to identify breast-cancer-specific small noncoding RNAs, which we have collectively termed orphan noncoding RNAs (oncRNAs). We subsequently discovered that one of these oncRNAs, which originates from the 3′ end ofTERC, acts as a regulator of gene expression and is a robust promoter of breast cancer metastasis. This oncRNA, which we have named T3p, exerts its prometastatic effects by acting as an inhibitor of RISC complex activity and increasing the expression of the prometastatic genesNUPR1 andPANX2 . Furthermore, we have shown that oncRNAs are present in cancer-cell-derived extracellular vesicles, raising the possibility that these circulating oncRNAs may also have a role in non–cell autonomous disease pathogenesis. Additionally, these circulating oncRNAs present a novel avenue for cancer fingerprinting using liquid biopsies. A novel orphan noncoding RNA species with tumor-specific expression across breast cancer subtypes promotes metastatic progression and holds potential for patient diagnosis.